1965
DOI: 10.1037/h0021888
|View full text |Cite
|
Sign up to set email alerts
|

The great response-style myth.

Abstract: Response styles (e.g., "yeasaying") must be distinguished from response sets (e.g., "dissimulation"). When this is done, and when those designs which permit inferences concerning response styles are distinguished from those which do not, the data accumulated to date must be interpreted as indicating that response styles are of no more than trivial importance in determining responses to personality, interest, and attitude inventories, current opinion to the contrary notwithstanding.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
85
1
1

Year Published

1967
1967
2018
2018

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 375 publications
(89 citation statements)
references
References 147 publications
2
85
1
1
Order By: Relevance
“…Eleven of the 13 items on their measure are keyed in the same direction; only 2 items are keyed in the other direction. Although it may be that when a true-false response format is used on an unbalanced test, total score variance attributable to response bias is minimal (e.g., Rorer, 1965), it is doubtful that when a six-point format is used (as Lennox and Wolfe did), response bias will be similarly minimal (e.g., Nunnally, 1967;cf. Cronbach, 1955).…”
Section: Evaluating the Intrinsic Validity Of Alternative Measuresmentioning
confidence: 99%
“…Eleven of the 13 items on their measure are keyed in the same direction; only 2 items are keyed in the other direction. Although it may be that when a true-false response format is used on an unbalanced test, total score variance attributable to response bias is minimal (e.g., Rorer, 1965), it is doubtful that when a six-point format is used (as Lennox and Wolfe did), response bias will be similarly minimal (e.g., Nunnally, 1967;cf. Cronbach, 1955).…”
Section: Evaluating the Intrinsic Validity Of Alternative Measuresmentioning
confidence: 99%
“…A three-process response model. Past work on response style (Baumgartner & Steenkamp, 2001;Cronbach, 1950;Rorer, 1965;Paulhus, 1991) showed that a respondent's use of a rating scale can be determined by variables that are unrelated to the attitude being measured. For example, some respondents may avoid using extreme response categories even if they feel strongly about a topic.…”
Section: Involvement Direction and Intensity In Likert Scalesmentioning
confidence: 99%
“…This real difference is likely to overwhelm what is typically a very small bias based on item directionality. The weight of past evidence together with our current analysis shows that acquiescence bias is a trivial influence in the responses to the RWA scale (Nunnally, 1978;Rorer, 1965).…”
mentioning
confidence: 99%
“…In a balanced, unidimensional scale, the acquiescence bias can potentially inflate correlations among pro-trait items and among con-trait items, and reduce the correlations between items with opposite wording. This tendency might be sufficient to suggest a two-factor solution in exploratory factor analysis though typically the acquiescence effect is of little substance (Nunnally, 1978;Rorer, 1965). Researchers 4 nonetheless tend to ignore factor solutions where the items heavily divided into protrait and con-trait factors.…”
mentioning
confidence: 99%